2012
DOI: 10.1016/j.jhep.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of cytochrome P450 2E1 (CYP2E1) in the development of high fat-induced non-alcoholic steatohepatitis

Abstract: Background & Aims Ethanol-inducible cytochrome P450 2E1 (CYP2E1) activity contributes to oxidative stress. However, CYP2E1 may have an important role in the pathogenesis of high-fat mediated nonalcoholic steatohepatitis (NASH). Thus, the role of CYP2E1 in high-fat mediated NASH development was evaluated. Methods Male wild-type (WT) and Cyp2e1-null mice were fed a low-fat diet (LFD, 10% energy-derived) or high-fat diet (HFD, 60% energy-derived) for 10 weeks. Liver histology and tissue homogenates were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
203
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(223 citation statements)
references
References 39 publications
18
203
0
2
Order By: Relevance
“…A common denominator in the pathogenesis of NAFLD is CYP2E1-dependent oxidative stress, as a key mechanism responsible for liver damage and disease progression [62]. In our study, quercetin protects liver against NAFLD by reducing CYP2E1 overexpression and subsequent oxidative stress, in agreement with results obtained in a similar in vivo model [63].…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetessupporting
confidence: 91%
“…A common denominator in the pathogenesis of NAFLD is CYP2E1-dependent oxidative stress, as a key mechanism responsible for liver damage and disease progression [62]. In our study, quercetin protects liver against NAFLD by reducing CYP2E1 overexpression and subsequent oxidative stress, in agreement with results obtained in a similar in vivo model [63].…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetessupporting
confidence: 91%
“…The more progressive form of NAFLD is termed NASH and is likely caused by a second or multiple hits from oxidative stress, inflammatory adipokines, activation of pattern recognition receptors, glucose intolerance, and insulin resistance (5). More recently, there have been significant studies that have shown the role of CYP2E1 in modulating the progression of NA-FLD to NASH via metabolic oxidative stress (1,21,22,30). In the present study, we used BDCM as a substrate for the generation of metabolic oxidative stress that aids in the progression of NASH (25).…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD shows increased CYP2E1 induction (1). We have previously shown that metabolic oxidative stress in NA-FLD/NASH causes lipid peroxidation primarily dependent on CYP2E1 in the liver (38).…”
Section: Nafld Potentiates Metabolic Oxidative Stress Via Cyp2e1mentioning
confidence: 92%
“…Metabolic oxidative stress in obesity-induced steatohepatitic injury is caused following increased CYP2E1 activity, mitochondrial uncoupling of the electron transport chain, or toxin metabolism following administration of hepatotoxic drugs (1,5,11,22). We and others (5,31,32) have shown that toxininduced steatohepatitis models produce metabolic oxidative stress.…”
Section: Steatohepatitic Injury In Obese Mice Is Associated With Incrmentioning
confidence: 96%